Monosodium glutamate induced oxidative stress in accessory reproductive organs of male Sprague-Dawley rats - Erni Norfardila Abu Hanipah; Nor Janna Yahya; Esther Mathias Ajik; Nur Afizah Yusoff; Izatus Shima Taib (Penerbit Universiti Kebangsaan Malaysia, 2018)
Monosodium glutamate (MSG) is widely used as a food additive but its excessive intake leads to oxidative stress of several organs. However, the oxidative effect of MSG on male accessory reproductive organs remains unclear. Therefore, the aim of this study was to evaluate the effect of MSG on the status of oxidative stress and morphological alterations in the male accessory reproductive organs such as epididymis, prostate glands and seminal vesicle of Sprague-Dawley rats. A total of 24 male Sprague-Dawley rats were randomly divided into three groups with 8 rats per group. Control group received distilled water (1 ml/kg) while MSG60 and MSG120 received 60 mg/kg and 120 mg/kg of MSG, respectively. All the substances were administered via force feed oral for 28 consecutive days. At the end of the study, the rats were sacrificed to obtain the accessory organs for biochemical analysis and histological observations. The SOD activity in the epididymis showed a significant increase in MSG60 and MSG120 compared to control (p < 0.05). The GSH levels in the epididymis of MSG 120 showed a significant reduction (p < 0.05) compared to the control group. The levels of MDA and PC in the epididymis and prostate gland of MSG60 and MSG120 showed a significant increased (p < 0.05) compared to the control group. Histological alterations were found in the epididymis and prostate gland of MSG treated rats. In conclusion, MSG at both doses induced oxidative stress in the epididymis and prostate gland of experimental rats.